Faktor faktor yang mempengaruhi pencegahan kecurangan (fraud) Pada BUMDes : good corporate governance, kesesuaian kompensasi dan pengendalian internal - Affan nurhaq; LMS Kristiyanti; Indra Lila Kusuma (Jurnal Akuntansi dan Pajak, 2027)
This study aims to determine the effect of Good Corporate Governance, Compensation Suitability, and Internal Control on Fraud Prevention in Village-Owned Enterprises (BUMDes) in Ngemplak District. This study used a quantitative approach. The study population consisted of 71 respondents from BUMDes administrators in Ngemplak District, Boyolali Regency. The sampling technique used was the Saturated Sampling method, with 71 respondents. The research data source was primary data using a questionnaire. Data analysis used descriptive methods of respondent data, validity tests, reliability tests, and classical assumption tests. Hypothesis testing included multiple linear regression analysis, F-tests, t-tests, and the coefficient of determination (R2). The results showed that Good Corporate Governance and Internal Control had a positive and significant effect on Fraud Prevention, while Internal Control did not have a positive and significant effect on Fraud Prevention. Keywords: BUMDes, Good Corporate Governance, Fraud, Compensation Suitability, Internal Control